Integral ecology and sustainable business - Jakobsen, Ove D.; Zsolnai, Laszlo (Emerald Publishing Limited, 2017)
This collection addresses the relationship between business, the natural environment, ethics, and spirituality. While traditional economic theory generally assumed firms maximize profits, it has long been acknowledged that other factors may be important to understanding firm activities. The role of ethics and spirituality in society is clearly significant, yet economists have traditionally had little to say on these topics and how they intersect with economic activity. Integral Ecology integrates concerns for people and the planet. It sees the world as systemically linked to ecology, economy, equity and justice and accessible through the natural and social sciences, arts and humanities. It links to sustainable business through frugal consumption, acknowledging the intrinsic value of nature, and adopting holistic management practices.This insightful study provides the insights of economists, business scholars, philosophers, lawyers, theologians and practitioners who are working in Europe, North America, and Asia. Their contributions highlight the relationship between integral ecology and sustainable business practices, and explore the meaning of sustainability in relation to both human and non-human life, offering a series of new and invigorating approaches to sustainable business practices and sustainability leadership.- Resumé vydavatel
Obsahuje index.
Keywords: podniky -- environmentální aspekty; udržitelný rozvoj; environmentální odpovědnost; business enterprises -- environmental aspects; sustainable development; environmental responsibility; sborníky; elektronické knihy; papers of several authors; electronic books